THE ROLE OF SOCIAL HOUSING IN THE RESIDENTIAL REAL ESTATE MARKET - KRYUKOVA, Irina; HAHARINOV, Oleksii; YAZLYUK, Borys; TSIUPAK, Volodymyr; DUDIAK, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Sharp fluctuations in demand in the residential real estate market and the general instability of its functioning, caused by the consequences of the military conflict in Ukraine, necessitate the search for practical tools to support and stabilize it. The purpose of this article is to determine the role and place of social housing in Ukraine’s residential real estate market within the context of modern trends in its development. The article identifies key features of the residential real estate market. These include: the uniqueness of purchase and sale objects, significant costs and barriers to entry/exit, high sensitivity to environmental factors, low elasticity of supply in the short term, social and state significance, and significant regional unevenness. The main price trends in the residential market are analyzed. The main trends inherent in it at this stage of development are identified. The analysis showed that the highest housing prices are in Kyiv, Lviv, Dnipro, Uzhhorod, and Odesa. The volume of demand and the dynamics of purchasing (or selling) residential real estate objects during wartime were studied. The results obtained showed the presence of significant regional differentiation in demand for housing, characterized by a critical drop in activity in frontline and occupied regions, as well as a sharp contrast in indicators between western areas and large agglomerations. At the same time, the Ukrainian housing market demonstrates the ability and results of adapting to existing realities. The role and significance of social housing in Ukraine’s modern housing market were studied. The nature of social housing was revealed through three plans: social, economic, and market. It was determined that the significance of social housing is evident in its role in ensuring the accessibility and stability of housing for a substantial portion of the country’s population. The social housing market forms a distinct segment. It serves as a complementary model to the traditional residential real estate market — the key features of social housing as a stabilizer of the residential real estate market have been determined. The attention is focused on the need for state regulation of the social housing market in Ukraine.